Upgrading lignin derived monomers over basic supported metal catalysts - Chaudhary, Richa; Dhepe, Paresh L. (Fuel, 2021)
Catalytic upgradation of aromatic monomers derived from lignin depolymerization is of high interest for the production of sustainable fuels and chemicals. Basic support has potential to provide advantages of better substrate-support interaction and reduced coke formation. Hence, we report the effect of various basic supports for metal catalysts (Pt, Pd, Ru) on the upgradation of phenol, guaiacol and eugenol. The complete hydrogenation product is achieved due to the strong interaction of the substrate with catalyst. Phenol is converted (55%) into cyclohexanol (49% yield) with low loading of Pt catalyst (1 wt%), supported by the higher TON of 1 wt% Pt/NaX (TON = 14844) than 3 wt% Pt/NaX (TON = 5128). Effect of basic support with moderate (NaX) and strong (CHT) basic strengths are corelated for the higher cyclohexanone formation. Presence of strong basic sites and higher TON of 3 wt% C-HT (TON = 6806) directs the significant substrate-support interaction. Catalytic activity and recyclability are supported by the comparable performance of recycle runs and characterizations of the fresh and spent catalysts.
Keywords: aromatic monomers; Hydrogenation; lignin; Solid bases; supported metal catalyst; Upgradation